Evaluation of the lactic acid consumption in yeast cultures by voltammetric means - Rodrigues, Astride (2005)
The voltammetric study of the lactic acid reduction was performed in media suitable for yeast growth, using platinum microelectrodes. The decrease of the voltammetric peak current from square wave voltammetry, variation of Ip, in cultures of the yeasts Candida utilis and Saccharomyces cerevisiae was related to both the growth time and cellular biomass. Either the imposed variations of medium composition or those resulting from cellular growth did not significantly affect the variation of Ip values. For both yeast species, similar specific growth rates were estimated from the variation of Ip and absorbance at 640 nm.